A Descriptive Study of Emotion Regulation in Students - Zalva Putri; Agung Nugraha; Muhammad Muhajirin (POTENSI : Journal of Education and Human Development, 2026)
Emotion regulation is an essential psychological ability that supports adolescents in managing emotional experiences during academic and social demands. This study aimed to describe the level of emotion regulation among ninth-grade students at SMP Negeri 1 Sukawening. A quantitative descriptive approach was employed. The participants consisted of 313 students selected using total sampling. Data were collected using an emotion regulation scale based on Gross’s theoretical framework. Descriptive statistical analysis was used to categorize students’ emotion regulation levels into high, moderate, and low categories. The results indicated that the majority of students demonstrated a moderate level of emotion regulation, suggesting that students possess basic emotional management skills that have not yet developed optimally. These findings highlight the importance of school-based guidance and counseling services in supporting the development of adolescents’ emotion regulation abilities.